The ecclesiology of Paul’s letters - Lehel, Lészai (2004)
God established the church, God called them out from the crowd that became alienated from Him. God has chosen Israel from the multitude of nations after the creation and Babel, although Israel was smaller than all the nations but God loved Israel and through them wanted to approach the other nations, too. Jesus compared the church to the building (temple), to the field, to the body and its members to the salt and light. He affirmed many times that His kingdom is not of this world and promised to His disciples the Comforter. The church is more an organism than an organization. A part of the church in Jerusalem flee from the growing prosecution and take with them the gospel, thus the Word of God is spread more and more to the end of earth. Jesus, the head of the church takes care of the first congregation, He strengthens, nourishes, encourages it and advises, stimulates, comforts it with His Holy Spirit. The church continues Christ’s work according to His command therefore it can be ascertained that the salvation-history is continued by the church on the earth. The purpose of the church is to struggle against the visible inimical powers and against all those forces that have untied their bonds to the kingdom of Christ. The body is still not complete; it has to grow. The growth is given by God and assisted by the Holy Spirit who holds together the body but all these have to happen in human beings. The first task of the church is the preaching of the gospel. The church has to strengthen its members in faith through the preaching, through the baptism and through the Lord’s Supper, in which it becomes clearly visible the character of Christ’s body. The church is corpus mixtum, the wheat and the weeds are growing together in it until the judgement day.